Peran environmental knowledge pada Gen Z dalam memoderasi hubungan antara green marketing dan green re-purchase Intention produk skincare - Gracea Febrinda Tjioe; Retno Ardianti (Nur Science Institute, 2025)
This study examines the effect of green marketing strategies on green repurchase intention among Generation Z consumers of locally produced, environmentally friendly skincare products in Indonesia. It also investigates the moderating role of environmental knowledge in this relationship. Using a quantitative approach, data were collected through a survey of 176 eligible respondents, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that green marketing strategies significantly influence green repurchase intention. Among the four green marketing elements, green product, green place, and green promotion have significant effects on green repurchase intention, whereas green price does not. In addition, environmental knowledge strengthens the relationship between green marketing and green repurchase intention, suggesting that the greater an individual’s understanding of environmental issues, the more likely they are to repurchase environmentally friendly products. These findings offer strategic implications for local skincare firms seeking to leverage green marketing to reach Gen Z consumers. For policymakers, the results underscore the importance of strengthening environmental education to foster awareness and sustainable consumption behavior.